Our Sports Clubs: The Sport-for-All Dream in Crisis?: Book Review of Our Kids: The American Dream in Crisis. By Robert Putnam. New York: Simon & Schuster, 2015, 400 pp.; ISBN: 1476769893. - Haudenhuyse, Reinhard (Social Inclusion, 2017)
This review investigates the potential implications of Putnam’s recent book Our Kids: The American Dream in Crisis for the field of social sport sciences. The main themes in Putnam’s Our Kids are class segregation and the widening ‘opportunity’ gap between the ‘have’ and ‘have nots’ in American society. The question can and needs to be asked: what the impact of class-based segregation has been on ‘our sport clubs’? Furthermore, Putnam also discusses the importance and unequal provision of Extracurricular activities. Putnam sees such activities as contexts for developing social skills, a sense of civic engagement and even for generating upward mobility. An important advantage of such activities is, according to Putnam, the exposure to caring adults outside the family, who can often serve as valuable mentors. However, throughout the book, Putnam uses a rather judgmental and moralizing language when talking about the parents of the ‘have nots’. The lesson that sport researchers can learn from this is to be sensitive and critical to moralizing approaches and deficiency discourses regarding the inclusion in and through sport of children and youth living in poverty.